2014
DOI: 10.1007/s12639-014-0593-5
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 gene expression in adventitial layer (fibrous layer) of hepatic ovine and bovine hydatid cysts

Abstract: Cystic Echinococcosis is a parasitic disease with cosmopolitan distribution caused by the tape worm Echinococcus granulosus. Fibrous layer is developed around the cyst as a host immune response reaction. The aim of this study was to evaluate the rate of IL-4 gene expression in fibrous layer of bovine and ovine hepatic hydatid cysts using quantitative technique of Real-Time PCR. In this descriptive study the samples of hydatid cyst fibrous layer were taken from 6 bovine and 6 ovine hepatic hydatid cysts. Sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Wang et al (2014) reported that E. granulosus infection significantly increased Th2 and T regulatory cytokine levels, in particular IL10, in lung tissues of infected mice. In another recent study (Dorosti et al, 2014), it has been shown that the adventitial layer of fertile ovine hydatid cysts in the liver show a high level of IL4 expression, suggesting that this cytokine, by inducing a Th2-type response, may play a key function in regulation of immune response in favor of the parasite. In the present study, we chose to evaluate lymphocyte subset populations in cysts that met the criteria for establishment according to Rogan et al (2014) in order to better define the local immune response in those cysts that have survived initial immune aggression, but that are not yet degenerated.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Wang et al (2014) reported that E. granulosus infection significantly increased Th2 and T regulatory cytokine levels, in particular IL10, in lung tissues of infected mice. In another recent study (Dorosti et al, 2014), it has been shown that the adventitial layer of fertile ovine hydatid cysts in the liver show a high level of IL4 expression, suggesting that this cytokine, by inducing a Th2-type response, may play a key function in regulation of immune response in favor of the parasite. In the present study, we chose to evaluate lymphocyte subset populations in cysts that met the criteria for establishment according to Rogan et al (2014) in order to better define the local immune response in those cysts that have survived initial immune aggression, but that are not yet degenerated.…”
Section: Resultsmentioning
confidence: 97%
“…It has been reported that early, establishmentphase cysts stimulate a Th1-type immune response, while established phase cysts are associated with a Th2, immunosuppressive type profile (Zhang et al, 2003). The adventitial layer, a host-derived fibrous capsule surrounding cysts which have been present for some time, has been suggested to play an important role in local immune regulation during infection (Dorosti et al, 2014). Lymphocyte infiltration is common within the adventitia, but there is little data on the nature of lymphocyte populations around stable cysts.…”
Section: Introductionmentioning
confidence: 99%
“…The adventitial layer is usually described as a fibrous layer due to the host's reaction to the parasite [9,[33][34][35][36][37][38][39], and several studies have described the cell composition of this layer. A study with fertile hydatid cysts found in the liver, showed that the adventitial layer has a significant amount of B lymphocytes, occasional polymorphonuclear cells and monocytes, however, they did no correlate this data with PSC viability, as the study was done in formalin-fixed, paraffin-embedded tissue samples [33].…”
Section: Discussionmentioning
confidence: 99%
“…Difference in cyst burden was evident only 6 months post‐infection, indicating that an equal number of cysts developed initially and killing occurred after cyst establishment. High levels of IFNÎł and IL‐4 (thus a mixed Th1/Th2 response) have been found to be produced from circumparasitic leucocytes and spleen cells of mice with dead cysts, while high levels of IL‐10 were produced by animals harbouring live cysts . Moreover, T‐regulatory and myeloid‐derived suppressor cells have been recently found to be systemically expanded in mice with established hydatid infection and in CE‐infected patients , and T‐regulatory cells have been recently identified in the periparasitic T‐cell infiltrate around ovine cysts .…”
Section: Immune Response In the Intermediate Hostmentioning
confidence: 99%